FACTORS CAUSING THE RISE OF ONLINE GAMBLING AND EFFORTS TO PREVENT IT IN THE SOCIETY ACCORDING TO THE ISLAMIC PERSPECTIVE - Jamal Rohman, Ahmad; M Rafli Husaeri; Dini Nurwasilah; Reiza Siti Awalia; Salman Alfarizi (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This study aims to analyze the factors causing the rise of online gambling in society and prevention efforts from an Islamic perspective. In the digital era, widespread internet access has facilitated the spread of online gambling, which is now accessed by various groups, including teenagers. Various factors, such as poverty, lack of employment opportunities, and the influence of the social environment, encourage individuals to engage in gambling practices. In addition, the wrong perception of the probability of winning also exacerbates this problem. From an Islamic perspective, gambling is considered a prohibited act, and prevention efforts need to be carried out through strengthening faith and piety, religious education, and community development. This study is expected to provide a deeper understanding of the impact of online gambling and the importance of social intervention to protect individuals, especially the younger generation, from detrimental behavior